FRI0508 Type and Timing of First Symptoms in Systemic Sclerosis: Prediction of Disease Course. (10th June 2014) - van den Hombergh, W.; van der Burgt, M.; van den Hoogen, F.; Fransen, J.; Vonk, M.
Abstract : Background: Systemic sclerosis (SSc) patients can be classified as diffuse cutaneous (dcSSc) and limited cutaneous disease (lcSSc), which are the main subtypes. Survival is shortened in both lcSSc and dcSSc (1) with a 5-year survival rate of 91 and 84% respectively (2). This is due to organ damage, which most often occurs in the first three years of the disease (1, 3), in dcSSc in as much as 70% (1) of the patients. In order to apply timely treatment in patients with high risk of early organ involvement, recognition of patients prone to development of dcSSc is necessary. Objectives: To determine whether the type and timing of the first non-Raynaud symptoms are predictive for the development of lcSSc or dcSSc. Methods: The Nijmegen Systemic Sclerosis database consists of consecutively included patients with systemic sclerosis according to the Leroy/Medgser or ACR-EULAR classification criteria. Patients have been classified as either lcSSc or dcSSc. Type of the first non-Raynaud symptom and time from Raynaud phenomenon to first non-Raynaud symptom and time to diagnosis were collected. Univariate and multivariate logistic regression were used to analyze the relation between first symptoms and development of lcSSc or dcSSc. Results: A total of 503 patients were included, 364 (72%) respectively 139 (28%) patients had lcSSc and dcSSc. Puffy hands (35%), scleroderma (22%), digital ulcers (16%), artralgia (14%) and dyspnea (8%) were the most common first non-Raynaud symptoms. The difference in time between Raynaud and first non-Raynaud symptom was 0.4 years compared to 0.0 years (p=0.001) between lcSSc and dcSSc. Of all patients with a time more than 3 months between Raynaud and non-Raynaud, 81% had lcSSc and only 19% dcSSc. Selected by univariate analysis (p<0.2) were sex, years between Raynaud en non-Raynaud, scleroderma, digital ulcers and dyspnea. Puffy hands (p=0.26) were still included because of its possible clinical significance. The resulting prediction model presented a sensitivity of 48% and a specificity of 83%. Conclusions: In this study, first steps are made in creating a prediction model for development of either diffuse or limited cutaneous SSc early in the disease course. Time between non-Raynaud and Raynaud is shorter in dcSSc, although not enough to predict disease course on its own. Meanwhile, it could be helpful knowledge for screening. References: Steen VD, Medsger TA, Jr. Severe organ involvement in systemic sclerosis with diffuse scleroderma. Arthritis and rheumatism. 2000;43(11):2437-44. Epub 2000/11/18. Nihtyanova SI, Tang EC, Coghlan JG, Wells AU, Black CM, Denton CP. Improved survival in systemic sclerosis is associated with better ascertainment of internal organ disease: a retrospective cohort study. QJM: monthly journal of the Association of Physicians. 2010;103(2):109-15. Epub 2009/12/08. Medsger TA, Jr. Classification, purpose. Philadelphia: Williams & Wilkins. 2004:17-28. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3204